BUDAYA ORGANISASI PADA SEKOLAH DASAR NEGERI KENAGARIAN PANYAKALAN KECAMATAN KUBUNG KABUPATEN SOLOK - Nadya Putri (Jurnal Bahana Manajemen Pendidikan, 2014)
Phenomena in the field suggests that organizational culture in a state that has not been ideal. This study aimed to obtain information about organizational culture in public elementary schools Kenagarian Panyakalan Solok. This descriptive type of research. The population in this study were all teachers in public elementary school Kenagarian Panyakalan Solok totaling 55 people.The sample size is determined by the table krejchi and gained as much as 48 people. Sampling technique using proportionate stratifed random sampling technique. The research instrumen was a questionnaire likert scale models that have been tested for validity and reliability. In general, the department of education in organizational culture in public elementary schools Kenagarian Panyakalan Solok quite well in the category with an average score of 3.53. Thus it can be said that the organizational culture is good. Key word: Organizational Culture